Impact of Fuel Subsidy Removal on Science Education in Nigerian Schools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This paper discussed the impact of subsidy removal on Science education in Nigerian schools. The paper employed the used of secondary data. The secondary data were collected from print resources and online publications. The paper concluded subsidy removal on petroleum product in Nigeria had affected science education generally and specifically, it had led to increment in the cost of science curriculum implementation, affected implementation of teaching and learning of science programme, led to increment in prices of laboratories resources and science instructional materials. Based on these problems identified, the paper recommended that the budget of education should be increase and more priorities should be given to science programme. Science teachers’ salaries should be increased and school buses should be distributed to all educational institutions. Government should subsidize science laboratories resources and instructional resources for effective implementation of science programmes in the schools.